Evaluation of phytoremediation in wastewater treatment with a focus on macrophyte selection, pollutant removal and biomass characteristics - Coimbra, Eder Carlos Lopes (2024)
The success of phytoremediation depends on carefully selecting plants to effectively remove water pollutants. The choice should consider the water type, specific pollutants, and treatment system conditions. This thesis comprises three technical-scientific papers. The first article conducted a review study on the relationship between environmental factors and the removal of iron (Fe), copper (Cu), and manganese (Mn), from wastewater, through phytoremediation. Emergent macrophytes showed the best results for Fe and Mn removal. Significant correlations were found between physical factors and the plants' ability to bioconcentrate Fe, Cu and Mn. Short exposures increased metal removal but hindered Fe and Cu absorption. Reduced light favored Cu and Mn removal, while lower pH favored Cu and Mn removal. High concentrations of phosphorus and dissolved oxygen increased Cu absorption in plants. In the second article, Lemna minuta, Landoltia punctata, Azolla microphylla, and Salvinia minima treated synthetic swine wastewater over a 10-day exposure period. Azolla microphylla experienced the least stress, and L. minuta showed the highest growth and lipid production. These two plants were more efficient in removing acute and chronic wastewater toxicity. All four plants exhibited removal rates exceeding 60% for COD and P-PO43-, and over 40% for N-NO3- and Cu. The Entropy-Fuzzy AHP TOPSIS method deemed Azolla microphylla the most suitable for treatment. This approach proved reliable in macrophyte selection, supported by individual evaluation and sensitivity analysis methods. The third article evaluated the impacts of LED light, considering its duration and intensity, as well as the phytohormone cytokinin, on Azolla microphylla's performance in treating synthetic swine wastewater. Results confirmed that both LED light and varying cytokinin doses influenced reduced concentrations of organic matter, metals, and sulfamethoxazole (SMX) in swine wastewater. Under optimal treatment conditions, Azolla removed COD (89.2% to 90.8%), N-NH4+ (72.6% to 91.2%), N-NO3- (84.4% to 88.6%), Cu (75.4% to 86.4%), SMX (77% to 79%), P-PO43- (54.1% to 59.9%), and dissolved organic carbon (67.4% to 71.3%). However, these conditions resulted in a moderate reduction for Zn. The influence of these factors varied for each pollutant, highlighting the importance of carefully considering treatment parameters. The research in this papers underscores the critical role of precise plant selection and treatment conditions in water remediation, emphasizing the need for multidisciplinary approaches and the potential for biomass reuse. Keywords: Phytoremediation; Biotope; Doehlert matrix; Multicriteria decision-making; Azolla; Swine Wastewater.